Pengembangan Adobe Flash Sebagai Media Pembelajaran Teorema Pythagoras Di Sekolah Menengah Pertama Negeri - Soleha, Reni; Mariani, Rina (Mathematic Education Departement, State Islamic University of Mataram, 2023)
Abstract This development research aims to determine the results of the development of Adobe Flash as a medium for learning the Pythagorean theorem for class VIII SMP. The product resulting from this research is in the form of learning media on Pythagorean theorem material with several sub-discussions, namely using the Pythagorean theorem to calculate the length of one side of a triangle if the other two sides are known, calculating the ratio of sides in a right triangle with angles of 300 and 600, and calculating the ratio of the sides of a right triangle with an angle of 450. The development model used in this study refers to the model developed by Sivasailam Thiagarajan, Dorothy S. Semmel, and Melvyn I. Semmel in 1974, namely the 4D model. This model consists of four stages of development namely define, design, develop, and disseminate or abbreviated as 4D. The results of this development research were obtained as follows: First, the validation stage by 3 expert validators covering aspects of programming, content (material), and display obtained an average expert validation result of 4.19 indicating that learning media (products) are in the